A New Bacterial Chemical Signal: Mapping the Chemical Space Used for Communication. Issue 4 (16th January 2014) - Schulz, Stefan
<x xml:space="preserve">Abstract</x> Sticking together: Genetic information, bioassays and chemical characterisation have revealed that photopyrones produced by insect pathogenic Photorabdus bacteria are new bacterial signalling compounds. They induce cell clumping behaviour in the bacterium.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>